2019
DOI: 10.1016/j.apenergy.2019.03.201
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of biomass supply system by combining computational methods – A review article

Abstract: As computing power increases, more complex computational models are utilized for biomass supply system studies. The paper describes three commonly used modeling methods in this context, geographic information systems, life-cycle assessment, and discrete-time simulation and presents bibliometric analysis of work using these three study methods. Of the 498 publications identified in searches of the Scopus and Web of Science databases, 17 reported on combinations of methods: 10 on life-cycle assessment and geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…On the contrary, LCA was first developed to account for environmental impacts before being developed to include economic (with LCC) and social (with S-LCA) impacts (Fauzi et al, 2019). MFA can evaluate the (Turner et al, 2016) EEIOA with information on material flows (Hawkins et al, 2007) None 22 13 2 156 SD Dynamic LCA of large systems; models market potential (Peng et al, 2018) Dynamic EEIOA and inclusion of feedback loops; models market potential (Cordier et al, 2017) Dynamic MFA revealing causal mechanisms within the system; models market potential (Gao et al, 2020) None 394 140 181 DES Dynamic LCA of small systems and their processes (Aalto et al, 2019) Technological details on EEIOA industrial sectors?…”
Section: Critical Analysismentioning
confidence: 99%
“…On the contrary, LCA was first developed to account for environmental impacts before being developed to include economic (with LCC) and social (with S-LCA) impacts (Fauzi et al, 2019). MFA can evaluate the (Turner et al, 2016) EEIOA with information on material flows (Hawkins et al, 2007) None 22 13 2 156 SD Dynamic LCA of large systems; models market potential (Peng et al, 2018) Dynamic EEIOA and inclusion of feedback loops; models market potential (Cordier et al, 2017) Dynamic MFA revealing causal mechanisms within the system; models market potential (Gao et al, 2020) None 394 140 181 DES Dynamic LCA of small systems and their processes (Aalto et al, 2019) Technological details on EEIOA industrial sectors?…”
Section: Critical Analysismentioning
confidence: 99%
“…In the area of mathematical modelling, several methods exist to analyze the processes undergoing at a log-yard [16][17][18]. In literature, one of the most adopted methods to model forestry processes is via discrete-event modelling (DEM), because many of these processes operate as a sequence of events.…”
Section: Introductionmentioning
confidence: 99%
“…Kishita et al [12] conducted a scenario analysis for a sustainable bioenergy business through a narrative storyline, which provides a consistent story as to what will happen to the business in the future. Aalto et al [13] refers to this study by Kishita et al as a way of using DES to assist with environmental impact assessment (CO 2 emission calculation). However, the authors note that there are disadvantages to their approach since the study omits the ripple effects of the actions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ABM, geographical information systems (GIS) are often used to analyse spatial information, which is important for collecting inventories in local contexts [15]. A review by Aalto et al [13] suggests that there are multiple benefits of coupling GIS and ABM with LCA; however, their study found no research that combines all three modelling approaches. There are however, a number of studies that have coupled ABM with LCA in the bioenergy sector [6,[16][17][18][19], and GIS with LCA [20][21][22].…”
Section: Introductionmentioning
confidence: 99%